Synergistic Activity of Capsaicin and Colistin Against Colistin-Resistant Acinetobacter baumannii: In Vitro/Vivo Efficacy and Mode of Action - Guo, Tingting; Li, Mengying; Sun, Xiaoli; Wang, Yuhang; Yang, Liying; Jiao, Hongmei; Li, Guocai (Frontiers in Pharmacology, 2021)
Acinetobacter baumannii is an opportunistic pathogen predominantly associated with nosocomial infections. With emerging resistance against polymyxins, synergistic combinations of drugs are being investigated as a new therapeutic approach. Capsaicin is a common constituent of the human diet and is widely used in traditional alternative medicines. The present study evaluated the antibacterial activities of capsaicin in combination with colistin against three unrelated colistin-resistant Acinetobacter baumannii strains in vitro and in vivo, and then further studied their synergistic mechanisms. Using the checkerboard technique and time-kill assays, capsaicin and colistin showed a synergistic effect on colistin-resistant A. baumannii. A mouse bacteremia model confirmed the in vivo effects of capsaicin and colistin. Mechanistic studies shown that capsaicin can inhibit the biofilm formation of both colistin-resistant and non-resistant A. baumannii. In addition, capsaicin decreased the production of intracellular ATP and disrupted the outer membrane of A. baumannii. In summary, the synergy between these drugs may enable a lower concentration of colistin to be used to treat A. baumannii infection, thereby reducing the dose-dependent side effects. Hence, capsaicin–colistin combination therapy may offer a new treatment option for the control of A. baumannii infection.